Coronary artery calcium in patients with atrial fibrillation undergoing catheter ablation – an opportunity to personalize cardiovascular and thromboembolic risk management. (14th October 2021) - Fernandes, S; Ladeiras-Lopes, R; Faria, R; Ferreira, W; Carvalho, M; Almeida, J; Fonseca, P; Oliveira, M; Goncalves, H; Ferreira, N; Primo, J; Fontes-Carvalho, R
Abstract: Introduction: There is a well-established association between atrial fibrillation (AF) and coronary artery disease (CAD). Coronary artery calcium score (CACS) is a helpful tool to refine cardiovascular risk stratification and guide strategies of cardiovascular (CV) primary prevention. Purpose: To evaluate the prevalence and clinical implications of CACS in terms of CV and thromboembolic risk stratification and preventive therapies, in patients with AF and atrial flutter (AFL) undergoing catheter ablation. Methods: Cross-sectional study including patients with AF/AFL undergoing multidetector computed tomography (MDCT) for ablation procedure planning from 2017 to 2019. Baseline clinical and demographical data were collected. CV and thromboembolic risks were evaluated based on the SCORE (Systematic Coronary Risk Evaluation) system and CHA2DS2-VASc score. CACS was assessed in patients without history of coronary artery disease using the Agatston method. Results: A total of 474 patients were included (441 with AF and 33 with AFL, mean age of 58±10 years, 62% male). Excluding those over 70 years of age (n=50, 11%), most patients had low (n=69, 22%) or moderate (n=188, 60%) CV risk and 277 (64%) patients had a CHA2DS2-VASc score ≥1 (male) or ≥2 (female). Overall, 265 patients (65%) were under chronic anticoagulation and 157 (39%) were under statin therapy. CAC was present in 254 (54%) patients and showed a multivessel distribution in 62% of the cases. The left main stem was affected in 81 (17%) patients and the left anterior descending artery in 211 (45%). Incorporating CACS>100 as a variable in CHA2DS2-VASc score (vascular disease parameter in patients without history of vascular disease) would have resulted in a significant score reclassification (n=87, 20%) and identification of new potential candidates for anticoagulation (n=12, 3%). Additional, anticoagulation would be indicated as a class IA recommendation in more 26 (6%) patients. Twenty three percent of patients with zero calcium were taking statins, and only 7% of patients with a CACS >300 were on high-intensity statin therapy. According to the recommendations and based on their CACS and current therapy, 103 (25%) patients would be candidates for statin therapy and 69 (17%) patients would be candidates for changes in the current statin therapy intensity (Table 1). Conclusion: In our study, more than half of the patients undergoing MDCT before AF/AFL catheter ablation had coronary calcium above zero. Our findings suggest that an opportunistic evaluation of CACS can be clinically valuable in thromboembolic risk stratification and management of preventive pharmacological strategies such as anticoagulation and statins. Funding Acknowledgement: Type of funding sources: None.